Experience with NESTROFT for screening for thalassemia trait/ minor: evaluation against CBC and HPLC in a high prevalence region in Saurashtra, Gujarat, India - Sorathiya, Varsha P.; Vachhani, Nishith A.; Nandani, Sanjeev L.; Vekariya, Daya J.; Kashiyani, Heena N.; Colah, Roshan B. (International Journal of Research in Medical Sciences, 2020)
Background: Hemoglobinopathies pose a significant health burden in India. Prevention programmes can significantly reduce this burden. Although sophisticated methods of screening for β thalassemia trait are available, a cheap and simple method is beneficial for population screening. Although the Naked Eye Single Tube Red Cell Osmotic Fragility Test (NESTROFT) has been evaluated in many studies, sample sizes were small in some and many earlier studies have not done complete blood count (CBC) and High-Performance Liquid Chromatography (HPLC) in all the cases. We evaluate the suitability of NESTROFT for detection of β-thalassemia trait in a high prevalence region in Saurashtra, Gujarat. Methods: Here, 1000 unrelated individuals were studied. NESTROFT, CBC and estimation of HbA2 and HbF or other hemoglobin variants were done by HPLC. Results: Prevalence of β thalassemia trait was 7.8% in this population. NESTROFT showed an overall sensitivity and specificity of 94.87 and 85.38 respectively for the detection of β thalassaemia trait. Using red cell indices (MCH <27 pg and MCV <80 fl), One β thalassemia trait with normal indices would have been missed. Among twelve individuals with other hemoglobinopathies (HbS, HbD, HbE, δβ thalassemia trait or HPFH), seven had a positive NESTROFT while three had normal MCV & MCH values. Conclusions: NESTROFT is a cost-effective sensitive test which does not require any equipment and can be done in remote areas. It remains a useful first line screening test when large populations have to be screened.